The Role of Tutors to Increase the Motivation of Homeschooling Primagama Students - Nursamsu, Ginanjar Bayu; Mulyono, Sungkowo Edy (Universitas Negeri Semarang, 2021)
This research aims to describe: The role of tutors to increase student learning motivation in equality education package c equivalent high school in homeschooling primagama Semarang, describes the supporting factors of tutors in increasing learning motivation students as well describe the inhibitory factors of tutors in increasing student learning motivation. The methods used in this study are qualitative descriptive, data collection using observation, interview, and documentation methods. The subjects in this study consisted of the head of homeschooling, 3 tutors, 3 students, Validity of data using triangulation techniques as well as in this study using data analysis techniques using Data Reduction, Presentation of Conclusion data and Verification. In this study obtained results including Student learning motivation in following the learning process consists of intrinsic motivation and extrinsic motivation, overall learning motivation Students have less good motivation in carrying out the learning process and learning activities. So, there needs to be increased motivation from inside and outside himself. The role of tutors to increase learning motivation can be seen from several indicators, namely: as informors, organizers, donors, initiators, motivators, mediators, facilitators, and evaluators in general tutors are able to carry out their roles so that tutors are able to provide and increase learning motivation to students.